CONCEPT AND CHARACTERISTICS OF TORTURE, CRIMINAL PROSECUTION, OR PUNISHMENT - Mamajanov , Abror (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Torture, criminal prosecution, and punishment represent critical components of legal and human rights systems, each influencing justice and societal norms. The conceptualization and characteristics of these practices are deeply rooted in legal, ethical, and sociopolitical frameworks, yet they continue to be contentious and complex subjects within criminal justice discourse. Despite extensive examination of these elements individually, there is a lack of comprehensive studies that integrate their conceptual foundations with contemporary applications and implications. This study aims to explore the definitions, characteristics, and interrelationships of torture, criminal prosecution, and punishment, assessing how they are conceptualized in modern legal systems and their impact on justice. The research finds that while torture is universally condemned and criminal prosecution and punishment are widely accepted components of justice, there is significant variation in their application and ethical considerations across different jurisdictions. This study contributes to the literature by providing an integrated analysis of these practices, highlighting how evolving legal standards and human rights norms are reshaping their application and understanding. The findings suggest that a nuanced understanding of these concepts is essential for developing more effective and ethical legal frameworks, ultimately enhancing the integrity and fairness of criminal justice systems globally.